Kaligrafi Al-Quran Sebagai Ornamen Masjid (Studi Living Quran di Masjid Nurul Imam) - Setiadi, Yudi (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
This study discusses the practice of using the verses of the Quran as ornamental mosques. This research is known as Living Quran. This study focuses more on the practical role of the Qur'an. In this case, the Qur'an not only serves as a guide. Al-Qur'an is used as decoration of the mosque in the form of calligraphy. This study uses a qualitative research method with the phenomenological approach of Alfred Schutz, in-order-to motive and because motive to uncover the reasons and objectives of making al-Qur'an calligraphy. The data of this study came from the results of observations, interviews, and documentation. This research found several findings. First, al-Qur'an is not only a guide, but transformed into decorating the mosque in the form of calligraphy. Second, the use of al-Qur'an verses as mosque ornaments indicates the mosque administrators' understanding and thought of the Qur'an. Third, because the motive for making calligraphy is the educational background of the founder of the pesantren mosque and the condition of the mosque congregation. Fourth, in-order-to motive calligraphy making is a trigger for the congregation to learn to read the Qur'an, the message of preaching, and for the congregation to read the Qur'an when visiting the mosque.